Stages of Transition to a Singular Economy - Yangibayev Umid Abdurashid o‘g‘li (American Journal of Botany and Bioengineering, 2024)
This article explores the concept of a singular economy, a hypothetical future where economies are unified across national borders. It outlines the potential stages of this transition, including increased globalization, policy harmonization, supranational institutions, a single currency, and a global market. The article also acknowledges the challenges associated with such a shift, such as loss of sovereignty, income inequality, and environmental impact.